2011
DOI: 10.1039/c0ay00390e
|View full text |Cite
|
Sign up to set email alerts
|

Container-less polymerization in acoustically levitated droplets: an analytical study by GPC and MALDI-TOF mass spectrometry

Abstract: Molecular masses and end groups of polystyrene (PS) formed in a novel container-less polymerization strategy, based on levitated droplets in an acoustic trap, were determined by Gel Permeation Chromatography (GPC) and Matrix-assisted Laser Desorption/Ionization Time of Flight Mass spectrometry (MALDI-TOF MS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Acoustic levitation has already been combined to several optical spectroscopy methods such as absorption, 1 fluorescence, 2,3 and Raman 4,5 spectroscopy, or X-ray diffraction. 6 In addition, acoustically levitated droplets allow container-less polymerization, 7 online reaction monitoring, 8 and in situ investigations of concentration induced effects, e.g. aggregation and crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic levitation has already been combined to several optical spectroscopy methods such as absorption, 1 fluorescence, 2,3 and Raman 4,5 spectroscopy, or X-ray diffraction. 6 In addition, acoustically levitated droplets allow container-less polymerization, 7 online reaction monitoring, 8 and in situ investigations of concentration induced effects, e.g. aggregation and crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Millimeter-sized acoustically levitated droplets have been characterized with a wide range of ionization techniques directly during the levitation of microliter droplets. These include variants of matrix-assisted laser desorption ionization (MALDI), , direct analysis in real time (DART) ionization, and field-induced droplet ionization (FIDI) . Both DART and FIDI have been used to follow reactive transformations in levitated droplets, although sequential measurements made on a single levitated droplet can significantly perturb its properties.…”
mentioning
confidence: 99%
“…The levitated liquid sample (5 μL) contained a mixture of analyte and ionic matrix and direct desorption was achieved via laser ablation at 337 nm. Subsequently, Leiterer et al 13 reported on reaction monitoring for the first time, studying a polymerization reaction directly in acoustically levitated drops. Analyte characterization was carried out offline via matrixassisted laser desorption ionization (MALDI)-TOF and gel permeation chromatography (GPC).…”
mentioning
confidence: 99%